2019
DOI: 10.35164/0554-2901-2019-5-6-36-39
|View full text |Cite
|
Sign up to set email alerts
|

Properties nanocomposites on the basis of vezuvian and the copolymer of ethylene with hexene

Abstract: Findings of investigation of infl uence of concentration and particle size of a connatural mineral of Azerbaijan vezuvian on the basic physical-mechanical properties of composites on the basis of a copolymer of ethylene with hexene are resulted. It is positioned that is comparative the best rheological and deformationlyof strength properties possess nanocomposites. It is shown, joint infl uence vezuvian and an amendment of dioxide of aluminium on qualitative characteristics nanocomposites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…All the results above allow confirming a "synergistic effect" in use of two mineral fillers. In this case, each filler contributes to the formation process of the permolecular structure and change of the complex properties of composite materials [14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…All the results above allow confirming a "synergistic effect" in use of two mineral fillers. In this case, each filler contributes to the formation process of the permolecular structure and change of the complex properties of composite materials [14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…An improvement in the strength, deformation, and rheological parameters, as well as in the thermaloxidative stability of the obtained nanocompo-sites, was revealed, which, apparently, is associated with the synergistic effect of the interaction of copper-containing nanoparticles with anhydride groups of MPE. It has been shown that nanocomposites based on PP/PE/NP can be processed both by pressing and by injection molding and extrusion [41][42].…”
Section: Other Composites For Various Purposesmentioning
confidence: 99%